Karakteristik Kecelakaan Transportasi Di Jalan Tol Ruas Jakarta-Cikampek - Mutharuddin, Mutharuddin (Warta Penelitian Perhubungan, 2010)
T1re advantages of toll road as the highwm; tend 111£lke tire driver tend to ignor the safehJ endangeredhimself and others. T1rerefore, it needs many efforts to minimize the possibility of an aaident. T1re tollroad accident frequently happened on tire Jaka.rta-Okampek toll road. The number and level of accidentson this toll road quite high. 'Dre approach used in this research is descriptive analysis of thepercentage bi; using priman; survei; and secondan; data collected from accident reports PT.JasaMarga which is tire depiction of the location of aaident research at Jaka.rta-Cikampek toll road.From tire research, tire causes of accidents at aaident prone areas in tire Jakarta-Cikampek toll road isdue to the driver's condition factor (79.7%), damage to vehicles (19.4%) and road conditions (0.14%).Descriptively driver who had an aaident on tire toll roads is largely caused bi; lack of anticipation(60.8%). The most frequent accident occun'ence time between of 12:00 to 18:00 P.M. T1re truck is avehicle h;pe that is often involved in aaiden.ts. Front of the rear end collision is tire most common h;peof aaident. Accidents more frequently in sunny ·weather conditions.At the Jakarta-Cikampek toll road there are some segments which include the accident spot km 12 -km 14 for Jakarta route toward Cikampek and km 10 - km 14, km 25 - km 27 and km 29 - km 30 fortire reverse direction. Dominating factor in the location of tire critical points including the driver's lackof anticipation, tire driver's drowsiness and the tires burst.